Characteristics and Adaptation Mechanisms of Saline-Tolerant Fodder Plants - Haryanto, Bambang; Wardi, Wardi; Puspito, Sigit; Harmini, Harmini; Nugroho, Wahyu Adi (Universitas Halu Oleo, 2023)
Coastal areas and small islands in Indonesia, reaching approximately 17,000 islands, will be directly affected by increasing sea levels, seawater intrusion, and salinization. This paper provides insight into salinity and its effect to plant, saline-tolerant animal feed crops' characteristics, adaptation mechanisms, and some proposed strategies to deal with salinity issues. This research was conducted through literature study and data were analyzed descriptively. Salinity affects the photosynthesis process, thereby decreasing the net Photosynthetic Rate (Pn), the stomatal aperture, Fv/Fm (efficient quantum), and quantum yield (light intensity/rate of photosynthesis). Salt-stressed plants can be seen from the severity by measuring the levels of Cl and Na in the roots, leaves, and chlorophyll. Plant tolerance to salinity is divided into two groups: glycophytes that are tolerant of low salt levels and halophytes that are tolerant of high salts. Salinity inhibits cell enlargement and division, increases plant mass, and increases protein and nucleic acid production. The plant adapts to saline stress, including osmotic adjustment, stress protein, free radical oxidative species (ROS) removal, ABA synthesis, and cross-adaptation. Increasing the productivity of animal feed in saline areas could be achieved in various ways by modifying water, land, chemical and biological properties, and farmer habits.